Melioidosis: A Neglected Cause of Community-Acquired Pneumonia - Virk, Harjeet Singh; Mukhopadhyay, Chiranjay; Wiersinga, W. Joost (Seminars in Respiratory and Critical Care Medicine, 2020)
Melioidosis, caused by the facultative intracellular gram-negative pathogen Burkholderia pseudomallei, is an emerging cause of community-acquired pneumonia across the tropics. The majority of patients present with pneumonia with or without sepsis, but localized and asymptomatic infection is also well recognized. Recent modeling and epidemiological studies have demonstrated the widespread presence of B. pseudomallei in otherwise unrecognized regions with a predicted mortality of 90,000 deaths worldwide. Innovative environmental studies are also uncovering how hydrodynamic, pedology, fauna, and weather events influence geographic distribution and incidence of melioidosis cases. Of concern is the changes associated with global warming, which will be conducive to B. pseudomallei in combination with the global diabetes pandemic. In fact, over 80% of patient developing melioidosis have underlying comorbidities. For this great mimicker, culture remains the mainstay of diagnosis and despite availability of other assays, challenges still remain in reducing time to diagnosis and avoiding misdiagnosis. With institution of timely antimicrobials such as ceftazidime and supportive intensive care, overall mortality can be reduced to 10%, although this can still be as high as 50% in poorly resourced areas. Promise is on the horizon with the first human vaccine trials being planned for 2021. Meanwhile new multiomics techniques are giving us a better understanding of the role of virulence and host–pathogen interactions on patient outcomes.
Keywords: melioidosis; Burkholderia pseudomallei; community-acquired pneumonia; sepsis; pathogenesis; antibiotics; chest X-ray; neglected tropical disease; biothreat; cystic fibrosis